Incorporation of the e - Government as a transversal axis in the Local Development Plans - Patiño, Israel (Advances in Social Sciences Research Journal, 2018)
E-government is part of the international mechanisms and initiatives for the proper use of information and communication technologies by governments in order to collaborate in the generation of information, Decision making, transparency and optimization of processes. However, local governments have problems in their implementation, use and exploitation, which limits their performance and sustainable impact. Therefore, a transversal axis in the Local Development Plans is proposed about e-government, and with this, collaborate for the satisfactory implementation of the Information and Communication Technologies